2017
DOI: 10.3390/w9090713
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Phytoplankton and Water Quality during Sustainable Restoration of an Urban Lake Used for Recreation and Water Supply

Abstract: Abstract:Groundwater intake near Lake Głębokie, situated in the city of Szczecin in Northwestern Poland, resulted in a distinct decrease in the lake water level. Water intake from a river and a neighboring urban area led to eutrophication and a strong cyanobacterial water bloom. Both the water intake and recreation were threatened due to the possible influence of cyanobacterial toxins. The lake was subjected to three sustainable restoration methods: aeration of sediment-water; iron addition to precipitate P, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 59 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…The water quality in other urban lakes was monitored by Kang et al [ 18 ], who found that the highest TN in Fengqing lake was 6.5 mg/L, while the COD Mn was 13.12 mg/L. A similar study conducted by Kozak et al [ 29 ] showed a TN of 4 mg/L, NO 3 − -N of 1.9 mg/L and a TP of 0.08 mg/L in the urban Lake Głębokie, Poland. The nutrients in the urban lakes of Xi’an City had higher levels than that of the largest freshwater lake in China, Lake Poyang, where the water quality was assessed using eutrophication and ecological indicators [ 30 ].…”
Section: Resultsmentioning
confidence: 94%
“…The water quality in other urban lakes was monitored by Kang et al [ 18 ], who found that the highest TN in Fengqing lake was 6.5 mg/L, while the COD Mn was 13.12 mg/L. A similar study conducted by Kozak et al [ 29 ] showed a TN of 4 mg/L, NO 3 − -N of 1.9 mg/L and a TP of 0.08 mg/L in the urban Lake Głębokie, Poland. The nutrients in the urban lakes of Xi’an City had higher levels than that of the largest freshwater lake in China, Lake Poyang, where the water quality was assessed using eutrophication and ecological indicators [ 30 ].…”
Section: Resultsmentioning
confidence: 94%
“…The diversity was higher than noted in shallow hypertrophic Syczyńskie Lake (Toporowska and Pawlik-Skowrońska 2014). An increase in the value of phytoplankton diversity during lake restoration is usually associated with the improvement of water quality, which has been demonstrated in several lakes (Gołdyn et al 2014;Kozak et al 2017Kozak et al , 2018. The intensity of the internal P-loading process was significantly lower in the littoral zone, where good oxygenation of water overlying the sediments was observed throughout the whole year.…”
Section: Discussionmentioning
confidence: 90%
“…In China, the main environmental parameter that influenced blooms was water temperature (Zhao et al, 2013;Wu et al 2017). The summer period was also related to an increase in blooms in China (Xu et al, 1992) and in Poland (Kozak et al, 2017). Another study (Henry and Santos, 2008) indicated that a temperature of 25ºC was most favorable for the excretion of ammonia and phosphorus by Chironomus larvae, which can be an indicator of increased eutrophication of the reservoir during summer, leading to increase in blooms in the water body.…”
Section: Resultsmentioning
confidence: 99%